Ἐνυπόγραφη μεταβυζαντινὴ εἰκόνα (1765) μὲ τὴν παράσταση τῆς Ἄκρας Ταπείνωσης ἀπὸ τὴν Κερμίρα τῆς Καππαδοκίας - Σκλείδα, Μαρία (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2015)
In this work Christ is depicted in the iconographic type known as the “Man of Sorrows”. The icon comes from the refugees’ heirlooms of Asia Minor, possibly from Kermira of Cappadocia. It is in almost perfect condition and measures 39,7×39,4 cm. The center of the depiction is occupied by the deceased Christ, while two lamenting angels, in smaller scale, stand behind. The lifeless Lord is inside the sarcophagus with his hands crossed. Between the two angels appears the nominative inscription of the icon, while on the right side of the sarcophagus the painter’s signature. The earliest known representation of this iconographic type is found in manuscripts and icons of the 11th and 12th centuries. Stylistically, the work is a combination of Byzantine and Western art. In the present icon there is an emphasis on the anatomy of the chest, a contrast between the strong body and the weak arms. The icon has an almost exaggerated expressiveness due to the white brushstrokes on the brownish-grey underpaint which create a dramatic lighting effect. Although the painter’s signature permits us to understand his name, it is not possible to identify him. The nominative inscription reveals the name of the donor, his origin and the date when the icon was produced.